PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013 S.D 2017 - Mufadhilah, Nurul; Makhdalena, Makhdalena; Nas, Syakdanur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the influence of cash turnover, receivable turnover, and inventory turnover on profitability both of simultaneously and partially at manufacturing companies of textil and garmen sub sector which is listing in the Indonesia Stock Exchange for period 2013 until 2017. This Study used ROA (Return On Asset) to measure profitability of the company. The population of this study is all of the companies of textil sector and garmen which is listing in the Indonesia Stock Exchange for 2013 until 2017 used census. The data used in this study was secondary data in the form of annual report. Data collection used documentation. The analysis of the data used multiple linier regression with the help of the program called SPSS (Statistical Package for Social Science). The result of this study showed that cash turnover, receivable turnover, and inventory turnover simultaneously had an influence on profitability. Cash turnover partially had a negative influence on profitability. Receivable turnover partially had a negative influence on profitability. Inventory turnover had a positive influence on profitability.Key words: Cash Turnover, Receivable Turnover, Inventory Turnover, Profitability and Return On Assets.